2012
DOI: 10.3109/09638288.2012.723790
|View full text |Cite
|
Sign up to set email alerts
|

The experience of amputation and prosthesis use for adults: a metasynthesis

Abstract: The findings provide a base from which to make suggestions regarding the provision of health rehabilitation services for this population. It is recommended that such services make greater use of psychological interventions and education, include patients' social support networks, use psychotherapy to support and develop positive coping strategies, and facilitate peer support from those who have already made positive adjustments to amputation and prosthesis use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
69
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(88 citation statements)
references
References 33 publications
8
69
0
6
Order By: Relevance
“…It was suggested that rejection of the prosthetic limb may occur if the participants could not get over the problems and adjust to wearing the prosthesis. These finding have been supported in a recent qualitative metasynthesis where several studies have described emotional ambiguity in the early stages following amputation where patients deal with the loss of their limb in the light of a future of prosthetic limb use [15]. In addition to factors related to successful prosthetic use, the qualitative metasynthesis results highlighted the importance of social considerations, such as social acceptance in terms of experiencing a positive attitude from family and friends, the importance of social comparison and positive social interactions.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…It was suggested that rejection of the prosthetic limb may occur if the participants could not get over the problems and adjust to wearing the prosthesis. These finding have been supported in a recent qualitative metasynthesis where several studies have described emotional ambiguity in the early stages following amputation where patients deal with the loss of their limb in the light of a future of prosthetic limb use [15]. In addition to factors related to successful prosthetic use, the qualitative metasynthesis results highlighted the importance of social considerations, such as social acceptance in terms of experiencing a positive attitude from family and friends, the importance of social comparison and positive social interactions.…”
Section: Introductionsupporting
confidence: 54%
“…Previous research within the area of amputation has started to develop a good understanding of the experience of amputation and prosthesis use for adults, which has important implications for the delivery of rehabilitation services [15]. However, no previous research has specifically explored the expectations of patients who have had an amputation and would be taking part in prosthetic rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…Two (Brown et al, 2014;Hollidge, 2013) of the three lowest scoring studies were published in relatively short reports compared with the other studies, implying they may have been restricted on the amount of information they could present. This reflects concerns by researchers that it is the quality of the research report that is being judged, not the quality of the research undertaken (Murray & Forshaw, 2013), and therefore highlights the risks of excluding studies on quality ratings alone. However, it is worth acknowledging that length of report did not correlate neatly with the quality ratings and some shorter studies achieved higher scores (e.g.…”
Section: Formation Of a Therapeutic Relationship 1-22mentioning
confidence: 99%
“…Regardless of etiology, a leg amputation is usually followed by major physical and psychosocial challenges that severely influence the person concerned (Murray & Forshaw, 2013;Norlyk, Martinsen, & Kjaer-Petersen, 2013;Ostler, Ellis-Hill, & Donovan-Hall, 2014;Washington & Williams, 2016). Reduced quality of life (Davidson, Khor, & Jones, 2010;Remes et al, 2010), significantly higher levels of social isolation, depression, and post-traumatic disorder (Horgan & MacLachlan, 2004;Remes et al, 2010) are reported particularly in the first year after the amputation (Phelps, Williams, Raichle, Turner, & Ehde, 2008).…”
Section: Articlementioning
confidence: 99%
“…Several studies have shown a direct link between locomotor capabilities with prosthesis and increased levels of autonomy, self-esteem, and improved social life (Jefferies, 2015;Murray, 2009;Murray & Forshaw, 2013;Schaffalitzky et al, 2011;Senra, Oliveira, Leal, & Vieira, 2012;Zidarov, Swaine, & Gauthier-Gagnon, 2009). However, not everyone will benefit from the provision of a lower limb prosthetics or will learn to master its use.…”
Section: Articlementioning
confidence: 99%